2017
DOI: 10.20473/jn.v12i2.4640
|View full text |Cite
|
Sign up to set email alerts
|

Development of Supervision Model based Experiential Learning for the Implementation of Patient Safety Goals at Teaching Hospital in Surabaya

Abstract: Introduction:One of the demands of clients who access health services is patient safety. The hospital is required to maintain and upgrade the patient's safety goals. Nurses as health care providers are at risk of making error and mistakes during their duty which may cause harm to the patient. The purpose of this study was to develop a model of supervision based on experiential learning in the implementation of patient safety goals. Method: This research used explanatory survey. The sample was from nurses who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Hospitals that obtain an international accreditation, must apply the conditions set for patient safety namely, Six Goal Patient Safety (Six Goal Patient Safety) which is also used by the PERSI Hospital Patient Safety Committee (KKPRS) and the Joint Commission International (JTI) 1 . There are 2 argues that nurses are one of the service providers who are at risk of making mistakes in patient safety because most of the patient safety standards / International Patient Safety Goal (IPSG) are applied by nurses, especially in the implementation of preventing falling patients.…”
Section: Introductionmentioning
confidence: 99%
“…Hospitals that obtain an international accreditation, must apply the conditions set for patient safety namely, Six Goal Patient Safety (Six Goal Patient Safety) which is also used by the PERSI Hospital Patient Safety Committee (KKPRS) and the Joint Commission International (JTI) 1 . There are 2 argues that nurses are one of the service providers who are at risk of making mistakes in patient safety because most of the patient safety standards / International Patient Safety Goal (IPSG) are applied by nurses, especially in the implementation of preventing falling patients.…”
Section: Introductionmentioning
confidence: 99%
“…Harmatiwi (2017) in her study found that the disobedience of supervisors on the protocol of supervision was quite high (60%) and the majority of supervisors do with indirect supervision. Effective supervision is carried out fairly, with feedback and follow-up thereafter (Maulidiawati, Nursalam, & Nihayati, 2017), in which implementation it is necessary to have communication and knowledge discuss. Knowledge discuss facilitates management in finding and solving problems that are happening through the knowledge of organizational members and sharing them throughout the organization (Lee, Kim, & Kim, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hospitals that obtain an international accreditation must apply the conditions set for patient safety namely, Six Goal Patient Safety (Six Goal Patient Safety) which is also used by the PERSI Hospital Patient Safety Committee (KKPRS) and the Joint Commission International (JTI). Nurses are one of the service providers who are at risk of making mistakes in patient safety because most of the patient safety standards / International Patient Safety Goal (IPSG) are applied by nurses 1 . The largest number of health workers in hospitals is nurses (40-60%), so nurses have an important role in determining the success of hospital accreditation.…”
Section: Introductionmentioning
confidence: 99%